Improving production and diet assimilation in fish-prawn integrated aquaculture, using iliophagus species - Franchini, Ariel C. [UNESP]; Costa, Gelcirene A. [UNESP]; Pereira, Stefany A. [UNESP]; Valenti, Wagner C. [UNESP]; Moraes-Valenti, Patricia [UNESP] (Elsevier, 2020)
In the integrated culture of pelagic fishes and benthic prawns, a large quantity of nutrients and energy remain in the pond bottom after harvest. This study assessed whether the inclusion of an iliophagus species, such as curimbata (Prochilodus lineatus), can take advantage of those resources and improves yield and diet use efficiency in tambaqui (Colossoma macropomum) and Amazon river prawn (Macrobrachium amazonicum) integrated aquaculture. A completely randomized experiment was designed with two treatments, and five replicates each of integrated systems: tambaqui and Amazon river prawn (TP) and tambaqui, Amazon river prawn, and curimbata (TPC). Ten 0.01-ha earthen ponds were used as experimental unities. Juveniles of tambaqui (3.93 ± 1.63 g) and Amazon river prawn (0.02 ± 0.02 g) were stocked in all ponds at a density of 3 and 11 individuals per m−2, respectively. Five ponds, selected at random, were also stocked with curimbata (3.11 ± 2.61 g) at a density of 5 individuals per m−2. Tambaqui was fed twice a day with an extruded commercial diet (32% crude protein) to apparent satiation. The prawn and curimbata were not fed. The experiment lasted 53 days. The presence of curimbata did not affect tambaqui performance, whereas reduced the production of prawn in ~25%. The inclusion of curimbata increased total species yield by ~35% (from 734 to 991 kg.ha−1) and decreased FCR by ~31% (from 0.61 to 0.42). These results indicate that a mud-feeder like curimbata can take advantage of the large quantity of nutrients and energy deposited in the bottom of freshwater pond aquaculture.
Keywords: Amazon river prawn; Curimbata; IMTA; Integrated aquaculture; Tambaqui